Corticosteroids induced avascular necrosis of hip, a "long COVID-19" complication: Case report. (October 2022) - Annam, Prathiba; Manda, Anusha; Myneni, Uday Krishna; Sahar, Aaminah Najmus; Prasad, Nagendra; Sam, Kezia K.; Sahu, Sambit; Reddy, Kiran Kumar
Abstract: Introduction and importance: Since it first surfaced, the new Coronavirus has multiplied and mutated into different forms, leading to a significant impact on people's lives. COVID-19's long-term impact is not completely known; It can only be hypothesized based on the prior outbreak of severe acute respiratory syndrome (SARS). Avascular necrosis (AVN) is one of these consequences, which if left untreated can lead to catastrophic events and bone collapse. It's important to remember that individuals who have recovered from COVID-19 infection are still at risk of developing AVN. The pathological findings in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection are very similar to those seen in severe acute respiratory syndrome coronavirus (SARS-CoV) infection. Case presentation: We present cases of 27 and 69-year-old men with no comorbidities admitted with complaints of bilateral hip pain post covid treatment with corticosteroids and antivirals. The diagnosis was established based on history, physical examination, and magnetic resonance imaging (MRI). Clinical discussion: The use of corticosteroids in the treatment of SARS-CoV-2 infection has saved many lives, and it is still advised for moderate to severe cases on a short-term basis. The long-term use of corticosteroids is associated with numerous side effects. One of the most prevalent side effects of steroids is avascular necrosis of the femoral head, which is aggravated by the disease process. Conclusion: Early detection of Avascular necrosis is very crucial in its management due to its high progression rate. Low therapeutic doses of corticosteroids with minimal effective duration remain the key to halting its occurrence. Highlights: Long-COVID is an aggregated term for long-term complications caused by SARS-Cov-2. Corticosteroid usage increased rapidly during the pandemic, which is said to halt the COVID-19 progression. Avascular necrosis (AVN) is one of the common side effects of extended corticosteroid use. Viral invasion combined with irrational steroid use is the driving force behind the occurrence of AVN in COVID-19 patients.